Jordan Corporate Governance Regulations : Comparative Study - Jordan Institute of Directors (World Bank Group, Washington, DC, 2015)
As the importance of Corporate Governance increases, an awareness and understanding of the different relevant regulations becomes of paramount value. The importance and value of Corporate Governance is not the core of this publication. The publication is built around the premise that Corporate Governance is important and increasingly becoming of significant importance for growth, continued success and sustainability. Accordingly, this publication aims to identify, highlight and summarize the different codes of Corporate Governance along with other relevant regulations that impact Corporate Governance that are available in Jordan. The authors intend to address the different codes with respect to the principles of Corporate Governance as defined by the Organization of Economic Cooperation and Development (OECD); namely: ensuring the basis for an effective Corporate Governance framework; the rights of shareholders and key ownership functions; the equitable treatment of shareholders; the role of stakeholders in Corporate Governance; disclosure and transparency; and the responsibilities of the Board. This comparative study will provide an overview of how each code (or relevant regulation) addresses the different principles and to what extent. Since certain Corporate Governance practices tend to overlap across different principles and cover broad practices, we have found that it would be best in this study to provide a detailed assessment of different practices and requirements based on different dimensions. The dimensions the authors use are those defined based on best practices as identified by the International Finance Corporation (IFC) as follows: commitment to Corporate Governance; board functioning; management control environment; disclosure and transparency; and shareholder and stakeholder relations.